2015
DOI: 10.1002/hbm.23027
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of resting-state magnetoencephalography power in sensor and source space

Abstract: Several studies have reported changes in spontaneous brain rhythms that could be used as clinical biomarkers or in the evaluation of neuropsychological and drug treatments in longitudinal studies using magnetoencephalography (MEG). There is an increasing necessity to use these measures in early diagnosis and pathology progression; however, there is a lack of studies addressing how reliable they are. Here, we provide the first test-retest reliability estimate of MEG power in resting-state at sensor and source s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 57 publications
6
48
0
Order By: Relevance
“…These findings are in accord with reliability data obtained for conventional lab-based EEG recording systems (Fernández et al, 1993, McEvoy et al, 2000, Salinsky et al, 1991, Burgess and Gruzelier, 1993, Corsi-Cabrera et al, 2007, Cannon et al, 2012. Reliability values from the portable EEG device also compare well to those reported for other commonly utilized functional measures, include resting (Zuo and Xing, 2014) and active fMRI (Bennett and Miller, 2010), PET/SPECT (Egerton et al, 2010, Catafau et al, 2008, and MEG (Martín-Buro et al, 2016). The reliability of conventional EEG systems has also been demonstrated over periods in excess of one-year (Näpflin et al, 2007, Hatz et al, 2014, Vuga et al, 2006, Gevins et al, 2012.…”
Section: Neurosky Thinkgear Retest Reliabilitysupporting
confidence: 85%
“…These findings are in accord with reliability data obtained for conventional lab-based EEG recording systems (Fernández et al, 1993, McEvoy et al, 2000, Salinsky et al, 1991, Burgess and Gruzelier, 1993, Corsi-Cabrera et al, 2007, Cannon et al, 2012. Reliability values from the portable EEG device also compare well to those reported for other commonly utilized functional measures, include resting (Zuo and Xing, 2014) and active fMRI (Bennett and Miller, 2010), PET/SPECT (Egerton et al, 2010, Catafau et al, 2008, and MEG (Martín-Buro et al, 2016). The reliability of conventional EEG systems has also been demonstrated over periods in excess of one-year (Näpflin et al, 2007, Hatz et al, 2014, Vuga et al, 2006, Gevins et al, 2012.…”
Section: Neurosky Thinkgear Retest Reliabilitysupporting
confidence: 85%
“…Such a repeated session would have provided a powerful control for natural variability over time in WM responses. We did not collect a second MEG session in controls because of the cost of MEG, and because there are many publications that have shown high test–retest reliability for MEG metrics (Ahonen, Huotilainen, & Brattico, 2016; Becker et al, 2012; Edgar et al, 2015; Martín-Buro, Garcés, & Maestú, 2016; Tan, Gross, & Uhlhaas, 2015). Importantly, Ahonen and colleagues (2016) found that neurophysiological responses during an N -back WM task were highly reliable.…”
Section: Discussionmentioning
confidence: 99%
“…For each parcel, the PSDs were averaged across subjects and runs, and then normalized such that the integrated PSD over the range 3-50 Hz equals 1. Analyses were performed on these cortical relative power maps, as in prior studies (Mellem et al, 2017;Hillebrand et al, 2012;Martín-Buro et al, 2016). The relative power map, defined for a particular frequency or band, provides a regional topography of the relative contribution of that frequency to the region's power.…”
Section: Meg Data Processingmentioning
confidence: 99%